Dairy Cattle Body Width Principal Component and the Correlation Level to Milk Yields as An Option for Selection Approach - S. Prabowo; Ş. İnal; M. Garip (Faculty of Animal Science, Bogor Agricultural University, 2023)
The body-width linear traits of dairy cattle affect their production capacity, particularly milk yield characteristics. Even so, the prominent dairy cattle body width linked to the milk yield up to this point is not explicitly articulated. Therefore, this exploration aimed to identify the best body width characteristic related to production capacity and milk yields as a selection criterion. The investigation samples were 121 heads of Friesian Holsteins raised in Indonesia. The total measured body width of dairy cattle was eleven variables. All parameters were examined on a centimeter unit scale. R software version 4.2.1 is synchronized with RStudio to implement principal component analysis (PCA), Pearson’s correlation, and regression. The PCA uncovered the shoulder width (SHW), chest width (CHW), loin width (LNW), rump width (RMW), thurl width (TLW), pin width (PNW), and rear udder width (RUW) as significant elements of body width. Afterward, the highest relationship to milk yield characteristics was controlled by the rear udder width (RUW) and teat back-view width (TBW) traits serially. Due to the TBW being disqualified from the first principal component, its place is taken by the PNW trait. As an epilogue, exploiting the RUW trait as the main priority for the lactation cow selection scheme is strongly advocated. Meanwhile, the PNW trait is the initial priority for calves and heifers.